A systematic review of the literature related to dropout for students with disabilities. Issue 3 (5th July 2022) - Foreman-Murray, Lindsay; Krowka, Sarah; Majeika, Caitlyn E.
Abstract: Students with disabilities drop out of high school at a higher rate than typically learning students, impacting their short and long-term educational and employment opportunities and making long-term financial stability less likely. In this review, the authors examined the indicators of dropout among students with high-incidence disabilities at the secondary level within correlational literature. Thirteen studies met inclusion criteria and suggest two important areas of focus in predicting and preventing dropout: school engagement and restrictive educational placement. Evidence from the literature indicates a significant positive relation between school-engagement and completion of high school and mixed indications for the connection between restrictive educational placement and school completion. The authors discuss implications for future research and practice.